THE PROBLEMS OF COURT SERVICES TYPES AND TARIFF BASED ON GOVERNMENT REGULATION NUMBER 53 OF 2008 - Muhammad Anis (Jurnal Hukum dan Peradilan, 2019)
The administration of judiciary is a form of state obligation as the fulfillment of civil rights for citizens. Various efforts in improving the quality of court services is continue to be encouraged through a modern judiciary with the development of information system technology, a necessity in the era of globalization. In addition, there is a paradigm shift in public services from traditional model to modern, efficient, effective and transparent public service. This was marked by changes in the form of services from manual performance models to information system automation and digitalization. The general practice of fulfilling public demands for government services continues to evolve rapidly following a series of measures (optimal), while the ability and capacity of service providers in meeting the demands of services of the developing community are slower follows the calculation series. As a result, there is a gap that requires continuous improvement through service innovation that requires sufficient funding. At present, the main government funding sources from the taxation sector are no longer able to cover all state expenditures. The trend of state income from the two sectors of state revenue, namely the tax and non-tax sectors in the last five years shows that the income from the tax sector continues to increase, while the Non-Tax State Revenue (PNBP) sector is relatively declining. Moreover, the provision of public services is endeavored to be free of charge. In judicial services, optimization of PNBP is based on the principle of administering justice (simple, fast and low cost) which has been regulated through Government Regulation Number 53 of 2008. The instructions for implementing government regulations have not been able to fully accommodate the activities and activities of case services, resulting in internal policies letter of the Secretary of the Republic of Indonesia No.268/SEK/01/V/2010 Regarding Time Remaining Cases and Case Fee Giro Services. Thus, it will be examined whether the demand deposit services and the remaining down-payment cases are the performance of the judiciary and whether it is possible for the Ministries/Institutions to self-determine through internal policies on the types of charges and non-PNBP tariffs set by PP No. 53 of 2008.